Molecular Cytogenetics - Heng, Henry H.Q; Liehr, Thomas; Yurov, Yuri; Iourov, Ivan
One of the world’s leading journals dedicated to cytogenetics and cytogenomics, Molecular Cytogenetics encompasses all aspects of chromosome biology and the application of molecular cytogenetic techniques in biology and medicine. Topic of interest include structural and functional organization of the chromosome and nucleus, genome variation, expression and evolution, chromosome abnormalities and genomic variations in medical genetics and tumor genetics. Molecular Cytogenetics is the official journal of the European Cytogeneticists Association.